Adopter des techniques d’acteur pour interpréter un texte en classe de langue - François Blondel (Corela)
Interpreting a dialog or a text is one of the practices in foreign language learning classes but it is often limited to mere repetition and memorization of sentences and intonation schemes which may result in a mechanical approach to the foreign language instead of a more personal approach which would allow more flexibility and self-correction capacity. That is why some acting techniques which teachers may not be aware of for lack of information can prove very useful to improve precision and fluidity in articulation and more variety in intonations, and therefore gradually adopting sounds, rhythm and melodies of the target language.